Satisfaction with teaching: a view from physical education students (Revista horizonte, 2016)
Objective: to identify students’ satisfaction for received education in academic modules of first semester 2015. Method: Male and females students from 1st, 3rd, 5th and 7th semesters in 2015 participate. Likert-type scale survey was used as instrument. Item 1 refers to Learning System with 22 questions. Item 2 emphasizes the designed competencies of the learning system with 7 questions. Item 3 focuses on different types of activities used in the module with 9 questions. Item 4 refers to development degree of skills and competencies with 9 questions, item 5 with one question requests for given time to the module and item 6 measures general satisfaction level. Results and conclusions: The students give a high satisfaction percentage (72%) to the received education by providing evidence of their satisfaction with the academic processes given by the Program and the University